Implementasi Kurikulum Merdeka di Sekolah Pedesaan: Tantangan dan Strategi dari Perspektif Guru SMP Negeri Satu Atap 1 Dolat Rayat - Eny Sihite; Lusinda Sigiro; Tri Indah Prasasti; Rotua Lumbantoruan; Talenta Sembiring; Yesika Simbolon (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Independent Curriculum is the latest education policy designed to provide students with learning freedom with a focus on developing competencies that are more flexible and student-centered. This study explains the implementation of the Independent Curriculum at SMP Negeri Satu Atap 1 Dolat Rayat, a rural school with various resource limitations. The research method used is qualitative research with data collection techniques through in-depth interviews with teachers, field observations, and school documentation. The results of the study based on the results of in-depth interviews with teachers, found the main challenges such as the low basic literacy skills of students, the limited facilities of learning support infrastructure, the low active participation of students, and the diversity of student backgrounds that affect the implementation of learning. In addition, limited support from parents and education policies are also obstacles. To optimize implementation, teachers implement strategies to strengthen literacy, continuous training, use contextual media, and build cross-stakeholder collaboration. This study confirms that the success of the Independent Curriculum in rural schools requires an adaptive contextual approach and synergy of all related parties.